2022
DOI: 10.3389/fphys.2022.1009647
|View full text |Cite
|
Sign up to set email alerts
|

Validation of in silico biomarkers for drug screening through ordinal logistic regression

Abstract: Since the Comprehensive in vitro Proarrhythmia Assay (CiPA) initiation, many studies have suggested various in silico features based on ionic charges, action potentials (AP), or intracellular calcium (Ca) to assess proarrhythmic risk. These in silico features are computed through electrophysiological simulations using in vitro experimental datasets as input, therefore changing with the quality of in vitro experimental data; however, research to validate the robustness of in silico features for proarrhythmic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Higher drug doses correspond to faster and larger increments in qInward values ( Li et al, 2017 ). Consistent with our findings, prior research has also highlighted the dominant role of qInward variability in convolutional neural network (CNN) classifiers for TdP risk classification ( Jeong et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Higher drug doses correspond to faster and larger increments in qInward values ( Li et al, 2017 ). Consistent with our findings, prior research has also highlighted the dominant role of qInward variability in convolutional neural network (CNN) classifiers for TdP risk classification ( Jeong et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…A previous study utilized the ToR–ORd model to evaluate the TdP metrics derived from single APs, intracellular calcium dynamics, and ionic charge obtained from the effects of drugs on the ToR–ORd ventricular cell model to classify TdP risks using ordinal logistic regression ( Jeong et al, 2022 ). However, using single TdP metrics from the in silico models for classifying the TdP risks is challenging to handle complex or non-linear relationships between independent and dependent variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al suggested the selection method of calibration drugs and calibrated the previous OLR model by validating it using two lab-specific datasets ( Han et al, 2020 ). In a previous study, we validated 12 promising in silico features using OLR, based on in-vitro datasets used in the AP simulation ( Jeong et al, 2022a ). In this study, we determined the CNN classifier using the variability of in silico features calculated using the Chantest dataset and validated the corresponding robustness using three merged in-vitro datasets.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we validated the robustness of 12 in silico features using an ordinal logistic regression (OLR) model by comparing the classification performances of metrics according to the used in-vitro experimental datasets ( Jeong et al, 2022a ). However, as the results of the OLR model using 12 in silico features were desirable, the single value of the in silico feature was perceived as limiting to classifying the three TdP risks.…”
Section: Introductionmentioning
confidence: 99%